2005
DOI: 10.1021/ma047373v
|View full text |Cite
|
Sign up to set email alerts
|

Radical Loss in RAFT-Mediated Emulsion Polymerizations

Abstract: Radical loss processes in RAFT-controlled emulsion polymerization are investigated using γ-initiated seeded emulsion polymerization of styrene in “relaxation mode”, i.e., following the rate of polymerization after removal from the radical source. This provides direct measurement of radical loss processes. A water-insoluble RAFT agent, 2-phenylprop-2-yl phenyldithioacetate, was transported to preformed seed particles using acetone, the acetone then removed, the particles swollen with monomer, and RAFT-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 75 publications
4
85
0
Order By: Relevance
“…This can easily be observed in Figure 7(b), where the dashed line representing dP n =dt ð Þ t is very closet to the thick full line representing R n . In the previous discussion, we concluded that, as expected, [21][22][23] the termination of shorter chains is favored with respect to that of longer chains by increasing the values of f, the ratio DP R n =DP crit and the polydispersity of the radical chains. Let us now see how this is connected to the deviation between the predictions of the conversion curves obtained by DP and the CLD model.…”
Section: Differences Between the Dp And The Cld Modelsupporting
confidence: 69%
“…This can easily be observed in Figure 7(b), where the dashed line representing dP n =dt ð Þ t is very closet to the thick full line representing R n . In the previous discussion, we concluded that, as expected, [21][22][23] the termination of shorter chains is favored with respect to that of longer chains by increasing the values of f, the ratio DP R n =DP crit and the polydispersity of the radical chains. Let us now see how this is connected to the deviation between the predictions of the conversion curves obtained by DP and the CLD model.…”
Section: Differences Between the Dp And The Cld Modelsupporting
confidence: 69%
“…As noted above, there is some debate as to whether the RAFT-adduct radical is capable of undergoing irreversible and/or reversible termination reactions (see Scheme 3) to any significant extent in normal polymerizing RAFT systems. [6,7,[76][77][78][79][80][81][82][83][84] Although computational quantum chemistry is not currently capable of predicting diffusion-controlled rate coefficients, computational calculations could nonetheless be used to calculate the chemically controlled component of the termination rate and establish a lower boundary to the termination rate coefficient. To this end, work is currently underway to Figure 1.…”
Section: Side Reactionsmentioning
confidence: 99%
“…We have discussed these challenges in our contributions to this topic [78][79][80] and in our comprehensive reviews of the RAFT process. [81][82][83] RAFT polymerization can be initiated by any source of free radicals including UV irradiation [84] and gamma irradiation [85] and can be performed over a wide range of temperatures, including room temperature.…”
Section: Thiocarbonyl Class Of Afctasmentioning
confidence: 99%